Ferroelectric and piezoelectric properties of (Bi1/2Na1/2)TiO3–BiFeO3 ceramics. Issue 1 (14th January 2016) - Fujii, Ichiro; Ito, Yutaka; Suzuki, Teppei; Wada, Takahiro
Abstract: Abstract : (1 − x ) (Bi1/2 Na1/2 )TiO3 – x BiFeO3 ( x = 0–0.9) ceramics were prepared and the ferroelectric and piezoelectric properties along with the crystal structure were investigated. The crystal system of the ceramics was rhombohedral with the R 3 c symmetry throughout the compositions. The rhombohedral distortion (90° − α), where α was the rhombohedral angle based on a pseudocubic perovskite cell, was minimized at x = 0.1, while the lattice constant increased linearly with x . Saturated ferroelectric polarization-electric field hysteresis loops were observed at x = 0–0.6. The coercive field was reduced at x = 0.05–0.2 and the high remanent polarization of 30–35 µC/cm 2 was obtained at x = 0–0.4. The piezoelectric constants d 33 and d 33 * (which was calculated from a unipolar strain–electric field curve) were maximized to 93 pC/N at x = 0.1 and 183 pm/V at x = 0.05, respectively. These results suggested that the increase in the piezoelectric properties was associated with the reduction in the rhombohedral distortion, which could be useful in development of high performance lead-free piezoelectric materials.